2008
DOI: 10.1007/s11626-008-9156-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, establishment, and characterization of ex vivo equine melanoma cell cultures

Abstract: Gray horses spontaneously develop metastatic melanomas that resemble human disease, and this is often accompanied with metastasis to other organs. Unlike in other species, the establishment of primary equine melanoma cultures that could be used to develop new therapeutic approaches has remained a major challenge. The purpose of the study was to develop a protocol for routine isolation and cultivation of primary equine melanocytes. Melanoma tissues were excised from 13 horses under local anesthesia, mainly from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The three horses showing a higher copy number in melanoma tissue than expected from their zygosity for Grey , were all euthanized possibly due to what might be internal melanoma metastases (ID1, ID2, ID3; Table 1, Figure 2B). mRNA from the tumour samples ID1 and ID2 were used for expression analysis in our previous study [19] and both samples had upregulated expression of STX17 and NR4A3 consistent with our interpretation that the copy number expansion detected in the present study may be relevant for tumour development. The melanoma cell lines showing a higher copy number than expected from the Grey genotype, Ho-Mel-A1 (Seltenhammer et al, in preparation) and M14 [20], have both been characterized as malignant, with M14 showing a high expression of the proliferating cell nuclear antigen PCNA [20], previously correlated with aggressive behaviour of human cutaneous malignant melanoma [19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The three horses showing a higher copy number in melanoma tissue than expected from their zygosity for Grey , were all euthanized possibly due to what might be internal melanoma metastases (ID1, ID2, ID3; Table 1, Figure 2B). mRNA from the tumour samples ID1 and ID2 were used for expression analysis in our previous study [19] and both samples had upregulated expression of STX17 and NR4A3 consistent with our interpretation that the copy number expansion detected in the present study may be relevant for tumour development. The melanoma cell lines showing a higher copy number than expected from the Grey genotype, Ho-Mel-A1 (Seltenhammer et al, in preparation) and M14 [20], have both been characterized as malignant, with M14 showing a high expression of the proliferating cell nuclear antigen PCNA [20], previously correlated with aggressive behaviour of human cutaneous malignant melanoma [19].…”
Section: Discussionsupporting
confidence: 90%
“…The present study has provided strong genetic support for our previous conclusion that the 4.6 kb duplication in intron 6 of STX17 causes Greying with age [19]. Firstly, the copy number expansion seen in tumours suggests that it may promote tumour progression.…”
Section: Discussionsupporting
confidence: 85%
“…13 Melan A expression in 1 equine melanocytic neoplasm and melanocytic cell lines has been reported. 3,25 PNL2 is a monoclonal antibody that recognizes a fixativeresistant melanocytic antigen in humans, dogs, and some laboratory animals, 2,7,8,16,18,24 the exact structure of which has yet to be identified. 10 In humans, PNL2 also labels angiomyolipomas and mature myeloid cells, including neutrophils, but not other nonmelanocytic tumors, including various carcinomas and sarcomas.…”
mentioning
confidence: 99%
“…13 Melan A expression in 1 equine melanocytic neoplasm and melanocytic cell lines has been reported. 3,25…”
mentioning
confidence: 99%
“…Although cosmetic concerns do not play an important role in daily veterinarian routine, there are implications for practice and research: tumors of melanocytic origin, the socalled white horse melanoma, present an area of intense clinical research interest. Here, tumors and melanoma cells derived from them have been characterized [28][29][30]. The underlying mutation has been looked into by Rosengren et al 2008 and identified as a 4.6 kb duplication in Syntaxin 17 on chromosome 25.…”
Section: Discussionmentioning
confidence: 99%